Handy divisions: Hand-specific specialization of prehensile control in bimanual tasks - Anvesh Naik; Satyajit Ambike (PLoS ONE, 2025)
When hammering a nail, why do right-handers wield the hammer in the right hand? The complementary dominance theory suggests a somewhat surprising answer. The two hands are specialized for different types of tasks: the dominant for manipulating objects, and the non-dominant for stabilizing objects. Right-handers wield the moving object with their right hand to leverage the skills of both hands. Functional specialization in hand use is often illustrated using examples of object manipulation. However, the complementary dominance theory is supported by wrist kinematics rather than object manipulation data. Therefore, our goal was to determine whether this theory extends to object manipulation. We hypothesized that hand-specific differences will be evident in the kinematics of hand-held objects and in the control of grip forces in right-handed individuals. Right-handed participants held two instrumented objects that were coupled by a spring. They moved one object while stabilizing the other object in various bimanual tasks. They performed motions of varying difficulty by tracking predictable or unpredictable targets. The two hands switched roles (stabilization vs movement) in various experimental blocks. The changing spring length perturbed both objects. We quantified the movement performance by measuring the objects’ positions, and grip force control by measuring grip-load coupling in the moving hand and mean grip force in the stabilizing hand. The right hand produced more accurate object movement, along with stronger grip-load coupling, indicating superior predictive control of the right hand. In contrast, the left hand stabilized the object better and exerted a higher grip force, indicating superior impedance control of the left hand. Task difficulty had a weak effect on grip-load coupling during object movement and no effect on mean grip force during object stabilization. These behavioral results demonstrate that complementary dominance extends to object manipulation, though the weak effect of task difficulty on grip characteristics warrants further investigation. Neurophysiological investigations can now examine the hemisphere-specific neural mechanisms underlying these behavioral differences.